Safety Evaluation of High Concrete-Faced Rockfill Dam Based on Site-Related Response Spectrum Using Scenario Earthquake - Kai-bin Zhu; Hong-jun Li; Xiao-gang Wang; Xiao-sheng Liu; Jian-ming Zhao (Advances in Civil Engineering)
To clarify how to arrive at earthquake ground motion parameters for use in evaluating the high rockfill dams during seismic loading conditions, as well as to evaluate reasonably the seismic response of dams subjected to strong earthquake, the differences of design response spectra determined by scenario earthquake and uniform hazard spectra theory are investigated in detail. Coupled with the safety evaluation of the Houziyan concrete-faced rockfill dam (CFRD) with a height of 200 m located in meizoseismal regions, comprehensive comparisons of key safety evaluation indices are performed using input motions determined from the abovementioned two design response spectra. The key safety evaluation indices include dynamic response acceleration, permanent deformation, safety of the impervious body, safety factor, and sliding displacement of the potential failure sliding body. Additionally, the ultimate seismic capability of the high CFRD is discussed based on the two response spectra. More considerable results can be achieved and offered to the engineers for the seismic design. It is obvious that the uniform hazard spectra, which are used to adopt in the safety evaluation of high CFRD, typically result in conservative evaluations and unnecessary economic cost for seismic design and reinforcements.